Development of Multi-Sector Partnership Strategies in Quality Planning for Holistic-Integrative Early Childhood Education - Widyatmike Gede Mulawarman; Andi Aslindah; Hasbi Sjamsir; Siti Halimah; Muhammad Ibnu Sa'ad; Ahmad Fitriadi (Journal of Pedagogy and Education Science, 2026)
The implementation of Holistic Integrative Early Childhood Education (PAUD HI) in Samarinda still faces challenges such as suboptimal cross-sectoral coordination, limited regulations, and low stakeholder participation, resulting in less than optimal service quality. This study aims to develop an effective partnership strategy in improving Holistic-Integrative Early Childhood Education (PAUD HI) quality. The research employed a Research and Development approach using the Plomp model, which consists of five stages: preliminary investigation, design, construction, evaluation and revision, and implementation. Data were collected through observation, interviews, documentation, and Focus Group Discussions. The study was conducted at TK Negeri 1 Samarinda and TK Islam Silmi Samarinda, representing public and private early childhood education (ECE) institutions. The findings reveal that the main challenges include weak partnership legalization, limited trained human resources, inconsistent stakeholder participation, concentrated coordination on principals, and limited funding. These conditions highlight the need for strengthening strategies through standardized systems, cross-sectoral coordination forums, capacity building, funding diversification, and integrated monitoring and evaluation. The developed strategy produced strategic documents, including a partnership roadmap, cross-sectoral Standard Operating Procedures (SOPs), and an integrated action plan. Expert validation indicated the strategy was highly valid (83.3%), while practitioner assessments showed it was highly effective (89.5%), with indicators covering contextual relevance, coordination feasibility, operational practicality, impact on service quality, and replication potential in other institutions. The study concludes that the success of the model requires structured, participatory, and sustainable multisectoral synergy, and the developed strategy can serve as a reference for local governments, ECE institutions, and stakeholders in developing comprehensive PAUD HI services.